2018
DOI: 10.1302/2058-5241.3.180005
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemia, healing and outcomes in proximal humeral fractures

Abstract: Interfragmental ischaemia is a prerequisite for the initiation of the inflammatory and immunological response to fracturing of bone.Intrafragmental ischaemia is inevitable: the extent of the initial ischaemic insult does not, however, directly relate to the outcome for healing of the fracture zones and avascular necrosis of the humeral head. The survival of distal regions of fragments with critical perfusion may be the result of a type of inosculation (blood vessel contact), which establishes reperfusion befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 58 publications
(52 reference statements)
0
11
0
5
Order By: Relevance
“…Based on earlier research, branches from the anterior circumflex humeral artery (ACHA) are the main blood supply to the HH, 10 , 13 , 16 but other researchers suggested that the posterior circumflex humeral artery (PCHA) may also contribute more toward the vascularization of the proximal humerus 3 , 8 . Lambert 17 suggested that the PCHA is of more importance to articular segment and tuberosity perfusion than the ACHA. Regardless of the contribution of blood supply to the HH, both of these arteries' intraosseous components and networks are potentially at risk during anchor placement.…”
mentioning
confidence: 99%
“…Based on earlier research, branches from the anterior circumflex humeral artery (ACHA) are the main blood supply to the HH, 10 , 13 , 16 but other researchers suggested that the posterior circumflex humeral artery (PCHA) may also contribute more toward the vascularization of the proximal humerus 3 , 8 . Lambert 17 suggested that the PCHA is of more importance to articular segment and tuberosity perfusion than the ACHA. Regardless of the contribution of blood supply to the HH, both of these arteries' intraosseous components and networks are potentially at risk during anchor placement.…”
mentioning
confidence: 99%
“…Chen et al observed that the average distances between the origin of the AHCA and the infraglenoid tubercle, the coracoid process, the acromion, and the mid-clavicular line were 26.9 mm, 49.2 mm, 67.0 mm, and 74.9 mm, respectively [17]. Anatomically, the medial, posterior-medial, and lateral regions are critical for the entry of the humeral circumflex artery branches, and should be avoided in placing retractors as well as implants [18]. Because the plate is positioned on the anteromedial face of the humeral head, there is less risk of intraoperative vascular damage.…”
Section: Discussionmentioning
confidence: 99%
“…Because the plate is positioned on the anteromedial face of the humeral head, there is less risk of intraoperative vascular damage. Additionally, Lambert showed that the head of the humerus can be completely revascularized, even when there is significant deviation or fragmentation of the posteromedial cortex, since significant anastomoses are distally present between the deltoid and ACHA [18]. As a result, at least four holes should be used for the medial plate, which should be located at the level of the insertion of the upper margin of the teres major muscle, just above the metaphyseal arterial ring.…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, open reposition and internal fixation of the PHF are prescribed, which may be ineffective due to osteoporosis. Despite the widespread clinical practice of new designs for osteosynthesis (plates with angular stability, blocked intramedullary rods, cannulated screws) and a number of publications, demonstrating the effectiveness of their application [7][8][9][10][11]. There is a high risk of avascular necrosis development in the head of humerus, nonunion of fragments, redislocation of fragments and metal migration which according to different authors can comprise up to 30 % [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%